Efektivitas pemberian hormon pertumbuhan rekombinan ikan kerapu kertang (Epinephelus lanceolatus, Bloch 1790) melalui perendaman dan oral terhadap pertumbuhan elver ikan sidat (Anguilla bicolor bicolor) - Alimuddin Alimuddin; Boyun Handoyo; Nur Bambang Priyo Utomo (Jurnal Iktiologi Indonesia, 2014)
Indonesian eel (Anguilla bicolor bicolor) has recently been cultivated intensively in Indonesia. The growth of Indonesian eel is slow. This study was performed to determine a proper delivery method of recombinant giant grouper (Epi-nephelus lanceolatus) growth hormone (rElGH) and observe aquaculture and nutrient related performances of Indonesian eel elver after rElGH treatment. Three delivery methods of rElGH, namely immersion, orally, and combination of immersion and orally were tested. The dosage of rElGH by immersion (12 mg L"1 water) and orally administration (30 mg kg-1 feed) were obtained in previous studies. Fish were maintained in 23 L glass aquaria for 120 days, at density of 45 fish in each aquarium. The results showed that higher (P<0.05) biomass of harvest (73.68±2.07 g) was obtained in immersion and oral combination treatment, by increment of about 102.9% compared to control (36.32±0.97 g). Administration of rElGH also improved protein and lipid retentions by 142.5%, and 720.0% compared to those of control, respectively (P<0.05). In addition, rElGH treatment increased appetite, while artificial feed conversion ratio (4.75) was 55.15% lower (P<0.05) compared to that of control (7.37). Combination of rElGH immersion and oral administrations also increased hepatosomatic index, and insuline-like growth factor-1 gene expression level. Thus, rElGH administration via immersion and oral combination was a proper method to improve growth of eel elver, and application of rElGH can be useful to increase aquaculture production. Abstrak Ikan sidat (Anguilla bicolor bicolor) telah dibudidayakan secara intensif di Indonesia. Pertumbuhan ikan sidat relatif lambat. Penelitian ini dilakukan untuk menentukan metode pemberian hormon pertumbuhan rekombinan ikan kerapu kertang (Epinephelus lanceolatus) (rElGH) untuk memacu pertumbuhan, dan mengevaluasi performa budi daya dan pemanfaatan pakan pada elver ikan sidat. Tiga metode pemberian rElGH diuji, yakni perendaman, oral, dan kombinasi perendaman dan oral. Dosis rElGH yang digunakan merupakan hasil penelitian sebelumnya, yakni 12 mg L-1 untuk me-tode perendaman dan 30 mg kg-1 pakan untuk metode oral. Ikan dipelihara dalam akuarium volume 23 L selama 120 hari, dengan padat tebar 45 ekor per akuarium. Hasil penelitian menunjukkan bahwa biomassa tertinggi (p<0,05) diper-oleh pada perlakuan kombinasi perendaman dan oral (73,68±2,07 g), sekitar 102,9% lebih tinggi daripada kontrol tanpa pemberian rElGH (36,32±0,97 g). Perlakuan rElGH juga meningkatkan retensi protein dan lemak, masing-masing 142,5% dan 720,0% lebih tinggi daripada kontrol (p<0,05). Selanjutnya, perlakuan rElGH meningkatkan nafsu makan, dan konversi pakan (4,75) sekitar 55,2% lebih rendah (p<0,05) daripada kontrol (7,37). Perlakuan kombinasi perendaman dan oral juga meningkatkan indeks hepatosomatik, dan ekspresi gen insuline-like growth factor I. Sebagai kesimpul-an, pemberian rElGH melalui kombinasi perendaman dan oral merupakan metode terbaik dalam memacu pertumbuhan elver ikan sidat, dan penerapan rElGH dapat digunakan untuk meningkatan produksi budi daya.